2017
DOI: 10.1016/j.arthro.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: Musculotendinous Junction Mattress Sutures Are Inefficient

Abstract: Medial row sutures placed at the musculotendinous junction are more likely to cut through the tendon than those sutures placed 10 mm lateral to the junction. Even if there is little tendon left, putting the stitches at the junction is a bad idea. In this instance, a single-row repair is better.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In cases with short tendons where one cannot pass the medial row sutures away from the MTJ, Barber recommended performing SR rather than a DR or a SB technique. 60 Shamsudin et al 59 reported similar short-term clinical outcomes in revision and primary rotator cuff repair. However, structural failure at 2 years was twice as likely in revision rotator cuff repair.…”
Section: Introductionmentioning
confidence: 95%
“…In cases with short tendons where one cannot pass the medial row sutures away from the MTJ, Barber recommended performing SR rather than a DR or a SB technique. 60 Shamsudin et al 59 reported similar short-term clinical outcomes in revision and primary rotator cuff repair. However, structural failure at 2 years was twice as likely in revision rotator cuff repair.…”
Section: Introductionmentioning
confidence: 95%